2017
DOI: 10.1186/s12985-017-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of HLA-DP and isolated anti-HBc are important subsets of occult hepatitis B infection in Indonesian blood donors: a case-control study

Abstract: BackgroundOccult hepatitis B infection (OBI) is defined as the presence of hepatitis B virus (HBV) DNA in the serum and/or liver in HBsAg-negative individuals. OBI is associated with the risk of viral transmission, especially in developing countries, and with progressive liver disease and reactivation in immunosuppressive patients. The objective of this study was to evaluate the relation of OBI to HLA-DP single nucleotide polymorphisms (SNPs) encoding antigen-binding sites for the immune response to HBV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
(78 reference statements)
0
20
0
Order By: Relevance
“…Additionally, rs872956 in HLA‐DPB1 was associated with HBV reactivation, and the mRNA expression of HLA‐DPB1 was lower in the HBV reactivated group after treatment with immunomodulatory agents . The rs3077 T in HLA‐DP was related to an increased risk of occult hepatitis B infection in an Indonesian population and HBsAg seroclearance in Caucasians . Collectively, these findings imply that a relationship exists between HLA‐DP variants and the host immune response after HBV infection …”
Section: Discussionmentioning
confidence: 91%
“…Additionally, rs872956 in HLA‐DPB1 was associated with HBV reactivation, and the mRNA expression of HLA‐DPB1 was lower in the HBV reactivated group after treatment with immunomodulatory agents . The rs3077 T in HLA‐DP was related to an increased risk of occult hepatitis B infection in an Indonesian population and HBsAg seroclearance in Caucasians . Collectively, these findings imply that a relationship exists between HLA‐DP variants and the host immune response after HBV infection …”
Section: Discussionmentioning
confidence: 91%
“…Subsequently, the genotypes of DPB1 * 05:01, 09:01, and DPB1 * 02:01, 04:01, and 04:02 were again found to be susceptible to HBV in Japanese [9] and Chinese [10] populations. The studies also found that some DPB1 alleles and rs9277535G related to weak HBV vaccines response [23] , low sensitive of HBV drug therapy [15] , incidence of occult HBV infection [24] , and also prone to hepatocellular carcinoma development [25] . In our study, we found the strongly association between rs9277535 and HLA-DPB1 alleles and HBV infection susceptibility.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we only included patients enrolled in Yogyakarta Province Hospital (RSUP Dr. Sardjito), a tertiary hospital that receives patients referred from several provinces in Indonesia. Furthermore, although the patients included were mostly Javanese, it is the most prevalent ethnic population in Indonesia (40.06%) [5].…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, liver cancer is the fifth most commonly diagnosed cancer and was the fourth leading cause of cancer-related deaths in 2012 [4]. Because of its endemicity of hepatitis B virus (HBV) infection, which is the third-highest prevalence worldwide, HBV is regarded as the leading cause of HCC in Indonesia [5]. A previous study performed in Indonesia demonstrated that most patients are diagnosed at intermediate to advanced stages (Barcelona Clinic Liver Cancer [BCLC] stage B or C), are relatively young (mean age, 54 years), and have a poor prognosis with a median overall survival of 138 days [6].…”
Section: Introductionmentioning
confidence: 99%